Counter clockwise rotation of cylinder with variable position to control base flows - Asadullah, Mohammed; Khan, Sher Afghan; Asrar, Waqar; Sulaeman, Erwin (Institute of Physics Publishing, 2018)
Experimental study of supersonic base flow at Mach 2 has been carried out to see the effect of cylinder when rotated counter clockwise inside the dead zone at variable locations near its base to control base pressure for different level of expansion for area ratio 9. Active cylinder of 2 mm diameter rotating counter clockwise when seen from top, is mounted as a controller. Three locations are chosen from the side wall of square duct namely at 2, 4, 6 mm respectively and 8 mm from square nozzle exit in the base region to mount the controller. Base pressure in recirculation zone and wall pressure along the square duct length has been measured with and without control. The experiments were carried out for NPR 2, 3, 6, 7.8 and 8.5. Cylinder when rotated counter clockwise as an active controller were found to reduce the base drag as high as 62 percent at NPR 8.5 when located near to duct wall and 50 percent when located away from duct wall for the same NPR. For perfectly expanded flows at NPR 7.8 the reduction in base drag was 53 percent near duct wall and 44 percent near duct wall. The active controller was up to 19 percentage effective for over expanded flows near to duct wall and up to 12 percent when located away from duct wall. Also, the control did not adversely affect the flow field. Key words: Wall pressure - base pressure - nozzle pressure ratio - active control